2007
DOI: 10.1074/mcp.m600367-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

The Secreted Signaling Protein Factor C Triggers the A-factor Response Regulon in Streptomyces griseus

Abstract: Members of the prokaryotic genus Streptomyces produce over 60% of all known antibiotics and a wide range of industrial enzymes. A leading theme in microbiology is which signals are received and transmitted by these organisms to trigger the onset of morphological differentiation and antibiotic production. The small ␥-butyrolactone A-factor is an important autoregulatory signaling molecule in streptomycetes, and A-factor mutants are blocked in development and antibiotic production. In this study we showed that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
(26 reference statements)
1
24
0
Order By: Relevance
“…showed that it compensates for a mutation that led to almost complete abolishment of production of A factor and regulates the production of many sporulation specific proteins [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…showed that it compensates for a mutation that led to almost complete abolishment of production of A factor and regulates the production of many sporulation specific proteins [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…The identity and mode of action of factor C, the morphological differentiation of S. griseus 45H and the effect of factor C on the differentiation of S. griseus 52-1 have been the subject of many publications (for a complete list see http://web.dote.hu/~sbiro/). Interaction between factor C and the regulon of S. griseus controlled by the best known c-butyrolactone autoregulator, A-factor (Ohnishi et al, 2005), has been described recently (Birkó et al, 2007).Since the two S. griseus strains (52-1 and 45H) differed in several substantial properties (Table 1), the origin of S. griseus 45H has often been questioned (Fehér & Szabó , 1978). Unquestionable evidence that the strain S. griseus 45H could not be a descendant of S. griseus 52-1 was obtained when the cloned factor C gene (facC) did not hybridize to the genomic DNA of S. griseus 52-1 (Birkó et al., 1999).…”
mentioning
confidence: 99%
“…The identity and mode of action of factor C, the morphological differentiation of S. griseus 45H and the effect of factor C on the differentiation of S. griseus 52-1 have been the subject of many publications (for a complete list see http://web.dote.hu/~sbiro/). Interaction between factor C and the regulon of S. griseus controlled by the best known c-butyrolactone autoregulator, A-factor (Ohnishi et al, 2005), has been described recently (Birkó et al, 2007).…”
mentioning
confidence: 99%
“…Our previous results (14) indicate a connection between two highly divergent types of signaling molecules and possible interplay between their regulatory networks. In preliminary experiments we observed characteristic differences between the extracellular proteomes of the strains that prompted detailed further analysis facilitated by the currently available DNA sequence of the genome of S. griseus IFO 13350 (17).…”
mentioning
confidence: 99%